Evidence-Based Policy Malang Creative Center dalam Meningkatkan Keunggulan Ekonomi Kreatif - Kartani, Kartani; Hayat, Hayat (Jurnal Ilmiah Administrasi Publik, 2023)
The aim of this research is to highlight the importance of Evidence-Based Policy (EBP) in public policy, especially in the creative economy sector. The aim of the research is to explore the role of the Malang Creative Center (MCC) in advancing the creative economy in Malang City. The research method uses a descriptive qualitative approach, with qualitative data analysis techniques involving interactive and continuous activities until the data is deemed to have included all the required information. This process involves steps such as data reduction, presenting data, and concluding results/verification. The analysis results show that MCC has made a positive contribution after operating since December 2022. The cross-sector partnership shows a commitment to encouraging creative economic growth in Malang City. The discussion underlines the importance of MCC in the context of Evidence-Based Policy (EBP). Data analysis includes a holistic picture of EBP implementation in MCC. The conclusion confirms that MCC, with the implementation of EBP, is the key to improving the creative economy in Malang City. As a result, this research provides an understanding of the implementation of EBP, especially in supporting the creative economy sector.